(untitled) (Altre Modernità, 2021)
This article explores border terms in Albanian using the example of the Dibra region. Dibra is an Albanian-Macedonian border region that originally formed a cultural, linguistic-dialectal and (extended) family unit and developed manifold divergences with the drawing of the borders in 1913 resp. 1925, including border terms. The article elaborates a great linguistic diversity to express spatial demarcations until the drawing of state borders at the beginning of the 20th century on a national basis, which was very foreign to local cultures. Therefore, no existing term proved suitable to express the new type of demarcation – the state borders. The local languages or dialects – in this case Dibra – still developed a number of new terms, most of which were borrowed. However, it also integrated the German term Mauer (‚wall‘) by means of a loan translation. This is because the borders of the state of Albania are perceived by the Albanians in a similar way to the German-German border as an internal national border that was drawn unjustly and therefore had to fall like its model in Berlin. The analysis of border terms in this article traces this development with the help of historical sociosemantics.